Cities, corporeality and consciousness - Ward, Graham (Stellenbosch Theological Journal, 2016)
This article seeks to explore the connections between our ability to live and work with symbols, our nature as a symbolic species, our physiologies, and our theologies, by examining the phenomenon of the (modern) city. It proposes that cities could be conceived of as ‘corporate’ expressions of human consciousness, that are founded on and continuously aim to purvey certain images and myths. These images and myth, it is argued, has been profoundly the work of a theological imagination. In an attempt to understand our modern (and seemingly secular) cityscapes, this article accordingly sets out to uncover some of the the particular theologies they articulate.